Processos de alfabetização das crianças e adolescentes da comunidade quilombola do arrojado - Silva, Maria Aurineide da (Universidade Federal Rural do Semi-Árido, 2020)
The aforementioned work concludes the course, presents a research on the literacy of children and adolescents from the quilombola community of Arrojado, the present work was carried out in this community located in the Municipality of Portalegre / RN. The interest in presenting this theme, was to show a research on literacy of a kilombola community developed by a researcher from this community. The general objective of the research was to understand how the teachers work in the context of the literacy of children and adolescents in the kilombola do Arrojado Community. As a theoretical basis, we refer to authors dealing with questions about literacy, rural education and quilombola education. The research was constituted as qualitative, using as a collection instrument the diagnosis of literacy, considers and resolving them in the classroom. There were two diagnoses with students from the Arrojado kilombola community, which pointed out the hypotheses of alphabetic writing they presented. The services provided to the manager and teachers of the municipal school that received this quilombola student sought the view of school management about this community and with teachers as the different methodologies according to the experience in the classroom. As a result, we realize that the school management has concerns in serving these students, both with regard to enrolled and alumni. The teachers pointed out the aspect of class absences of students from the community and indicated a preference for this methodology according to the unified planning. Thus, it is concluded that it is of great importance to research on the learning of kilombola communities, since it is generally far from large urban centers and quilombola literacy processes are not discussed within the academy.
Keywords: Alfabetização quilombola; Educação do campo; Educação quilombola; Kilombola literacy; Field education; Kilombola Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL